2002
DOI: 10.1023/a:1013884426692
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Astrocytic tumors are the most common human brain tumors. Establishment of tumor grade is a key determinant both in the choice of a therapeutic approach and in the prognosis. The diagnosis of astrocytic tumors is currently determined following histopathological analysis. The identification of molecular markers would offer a complementary tool for characterizing tumors with respect to their clinical behavior. In this study we determined the expression levels of 3 small GTP binding proteins (RhoA, RhoB and Rac1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Consistent with this, fibroblasts derived from RhoB null mice are resistant to both physical and chemical induced apoptosis [12], and RhoB induces apoptosis if overexpressed in transformed cells [9]. RhoB expression is often suppressed during tumor progression which may impair normal apoptotic signaling, and thus, support tumor growth [13][14][15]. It has been previously reported that RhoB suppresses NF-κB signaling in murine fibroblasts which may account for this propapoptotic activity [20].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Consistent with this, fibroblasts derived from RhoB null mice are resistant to both physical and chemical induced apoptosis [12], and RhoB induces apoptosis if overexpressed in transformed cells [9]. RhoB expression is often suppressed during tumor progression which may impair normal apoptotic signaling, and thus, support tumor growth [13][14][15]. It has been previously reported that RhoB suppresses NF-κB signaling in murine fibroblasts which may account for this propapoptotic activity [20].…”
Section: Discussionmentioning
confidence: 71%
“…Although several studies suggest that RhoB may also promote cell growth, and possess the properties of an oncogene [9,10], most studies suggest that it may in fact be a tumor suppressor [11,12]. RhoB expression is low in many tumor types [13][14][15], and knockout mice display increased susceptibility to carcinogenic agents [12]. Recent studies suggest that a change in prenylation status of RhoB may account for the proapoptotic and antineoplastic effects associated with farnesyl transferase inhibitors (FTIs) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Images are representative of at least four separate experiments yielding similar results different types of glioma cells; however, no comparisons with primary human astrocytes were previously made. Forget et al (2002) recently reported that immunodetected caveolin-1 protein expression in astrocytic tumors of various grades was not significantly different from that in the normal brain. In glioblastoma cells examined in this study, increases in caveolin-1 mRNA and protein expression were both correlated with the more transformed cellular phenotype, and consistently detected in glioblastoma tumors, suggesting a role for caveolin-1 in glial tumorigenesis.…”
Section: Discussionmentioning
confidence: 93%
“…Although some GTPase family members, such as RhoA, Rac1, and Cdc42, promote oncogenesis, invasion, and metastasis, there is emerging evidence that points to a tumor-suppres-sive role for RhoB (9 -12), notably through its role in the apoptotic process (9,13,14). Besides the fact that ectopic expression of RhoB inhibits tumor growth (9,15) and melanoma metastasis in a mouse model (16), we (17) and others (18,19) have also shown that RhoB expression decreases substantially with the aggressiveness of lung, head, and neck carcinomas and glioblastomas.…”
mentioning
confidence: 87%